UNAUTHORIZED CONTROL OF LAND AND BUILDINGS BY STATE SENIOR HIGH SCHOOL 5 PEMATANG SIANTAR BASED ON CIVIL LAW PERSPECTIVE - Nurva Alifia Sinaga; Mhd Syukran Yamin Lubis (Inspiring Law Journal, 2026)
Unlawful possession of land and buildings is a civil law issue that frequently gives rise to disputes, including when carried out by state institutions. This phenomenon indicates a potential conflict between public interests and the protection of individual civil rights. This study examines the unlawful possession of land and buildings used by Pematang Siantar State Senior High School 5. This study focuses on the legal regulation of land and building possession under civil law and the legal status of unlawful possession from the perspective of unlawful acts.The results of the study indicate that the control of land and buildings by SMA Negeri 5 Pematang Siantar continues even though there has never been a legal transfer of ownership rights from the owner to the government. This control is only based on a temporary loan agreement and does not transfer ownership rights to the land and buildings in question. This condition causes land control to be carried out without a strong legal basis, especially when the owner or heirs have expressed objections and requested a clear legal settlement. From a civil law perspective, this action fulfills the elements of an unlawful act as regulated in Article 1365 of the Civil Code because it causes harm to the legitimate rights owner. The court decision emphasized that the public interest in the field of education cannot be used as a justification for ignoring the property rights of others. Therefore, this study emphasizes the importance of legal certainty, protection of property rights, and government responsibility in managing educational assets to prevent civil harm to the community.